Factors associated with family resilience during pregnancy among inner-city women. Issue 10 (October 2015) - Lennon, Suzanne L.; Heaman, Maureen
Abstract Objective family resilience refers to the ability of a family group to adapt to challenging circumstances. For families residing in the inner-city, the concept of resilience is of particular salience as these families often encounter multiple stressors. The purpose of this study was to determine the factors associated with low family resilience during pregnancy among inner-city women. Design secondary analysis of data from a case-control study of factors related to inadequate antenatal care. Setting/participants participants consisted of 603 postpartum women who gave birth to a live infant and resided in one of eight inner-city neighbourhoods in Winnipeg, Manitoba. Methods participants were designated as having low family resilience (n=155) or moderate to high family resilience (n=448) based on scores on the Family Hardiness Index. Univariate analyses were conducted to explore the association between a variety of factors during pregnancy and family resilience, and crude odds ratios (OR) and 95% confidence intervals (CI) were calculated. Factors significant at p<.10 were then entered into a multivariate logistic regression model, yielding adjusted ORs and 95% CI. Results the following factors were significantly associated with low family resilience among pregnant inner-city women in the final model: maternal age <25 years (AOR 1.69), low self-esteem (AOR 2.82), high perceived stress (AOR 3.01), alcohol use during pregnancy (AOR 3.20), and low interpersonal support (AOR 6.24). Key conclusions inner-city women who are young or have low self-esteem, high perceived stress, low interpersonal support, or who use alcohol during pregnancy are more likely to report lower levels of family resilience. Implications for practice midwives have the opportunity to develop ongoing relationships with their clients and families. As such, they are in an excellent position to understand the specific needs and strengths of individual families and foster the abilities of these families to strengthen and support resilience.